'Cylindrocarpon' and Ilyonectria Species Causing Root and Crown Rot Disease of Potted Laurustinus Plants in Italy. Issue 7 (22nd August 2014) - Aiello, Dalia; Guarnaccia, Vladimiro; Epifani, Filomena; Perrone, Giancarlo; Polizzi, Giancarlo
Abstract During the 2012 and 2013 growing seasons, a disease was detected on potted laurustinus (Viburnum tinus) plants in two nurseries located in the Catania province (eastern Sicily, Italy). 'Cylindrocarpon'‐like species were consistently recovered from crown rot and stem rot tissues. Based on morphological characteristics, DNA sequencing and phylogenetic analysis of β‐tubulin (TUB), histone H3 (HIS3) and translation elongation factor‐1α (TEF‐1 α) gene sequences, the fungi associated with symptomatic tissues were identified as 'Cylindrocarpon' pauciseptatum, Ilyonectria novozelandica and I. torresensis. Koch's postulates were fulfilled by pathogenicity tests carried out on potted V. tinus cuttings. To our knowledge, this is the first report worldwide of 'C.' pauciseptatum, I. novozelandica and I. torresensis causing disease on V. tinus.